2016
DOI: 10.1002/rsa.20652
|View full text |Cite
|
Sign up to set email alerts
|

Constructing near spanning trees with few local inspections

Abstract: Constructing a spanning tree of a graph is one of the most basic tasks in graph theory.Motivated by several recent studies of local graph algorithms, we consider the following variant of this problem. Let G be a connected bounded-degree graph. Given an edge e in G we would like to decide whether e belongs to a connected subgraph G consisting of (1+ )n edges (for a prespecified constant > 0), where the decision for different edges should be consistent with the same subgraph G . Can this task be performed by ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…On the other hand lower bounds in this model are almost nonexistent. In fact, the only lower bound shown directly in the centralised local model is for the spanning graph problem in which the CentLOCAL algorithm computes a "tree-like" subgraph of a given bounded degree graph [16,17].…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand lower bounds in this model are almost nonexistent. In fact, the only lower bound shown directly in the centralised local model is for the spanning graph problem in which the CentLOCAL algorithm computes a "tree-like" subgraph of a given bounded degree graph [16,17].…”
Section: Related Workmentioning
confidence: 99%
“…Formally, an (ϵ,q) ‐local sparse spanning graph algorithm makes at most q queries to the incidence‐lists representation of the (bounded‐degree, connected) input graph G , and provides query access to a connected subgraph G of G that has fewer than (1+ϵ)n edges. The question of which graphs have a local spanning graph algorithm that uses only a constant number of queries was studied in , where it was shown that the answer is given by the same hereditary notion of expansion considered in the current paper. A graph is said to be f‐non‐expanding if every t ‐vertex subgraph H has edge expansion at most f ( t ).…”
Section: Applications Of Main Resultsmentioning
confidence: 92%
“…Motivated by the growing literature on local algorithms (see Rubinfeld et al and the references in ), let us consider the problem of constructing a spanning tree of a graph G in a local manner. By this we mean being able to decide if a given edge of G belongs to the tree in constant time (and in particular, without constructing the entire tree).…”
Section: Applications Of Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations